Exercise Interventions for Individuals With Neurological Disorders: A Systematic Review of Systematic Reviews. (October 2019) - Lai, Chien-Hung; Chen, Hung-Chou; Liou, Tsan-Hon; Li, Wei; Chen, Shih-Ching
Abstract : Abstract: Fall prevention requires a multifaceted approach that should include individual risk assessment and intervention strategies. Exercise interventions may mitigate most risk factors for falls (eg, balance impairment, gait impairment, and muscle weakness). Numerous systematic reviews or meta-analyses have assessed the effectiveness of exercise interventions among people with various types of neurological disorders; however, the evidence obtained has not been synthesized into an overview. Therefore, the present systematic review assessed systematic reviews of exercise intervention for fall prevention among people with neurological disorders. The research sources were the Cochrane Database of Systematic Reviews, PubMed, and Embase. Eligible studies were selected, and data were extracted independently by two reviewers. A total of 15 studies (six systematic reviews and nine meta-analyses) were included. These systematic reviews examined in this study have demonstrated that exercise interventions reduced the number, frequency, and rate of falls among people with neurological disorders, including cognitive impairment, dementia, and Parkinson disease. Furthermore, the current study presented insufficient evidence regarding the effectiveness of exercise interventions for fall prevention among people with stroke, multiple sclerosis, and diabetes mellitus with polyneuropathy. Therefore, additional investigations are necessary to evaluate the effectiveness of exercise for fall prevention among people with multiple sclerosis, stroke, and diabetes mellitus with polyneuropathy. Abstract : Supplemental digital content is available in the text.